PENGARUH FDR, NPF DAN CAR TERHADAP PEMBIAYAAN MURABAHAH (Studi Kasus pada Bank Umum Syariah di Indonesia Periode 2015-2019) - Anisa Octaviani Noegraha; Nana Diana (Jurnal Riset Akuntansi, 2021)
This study aims to see the effect of deposit financing (FDR) (X1) non-performing financing (NPF) (X2) Capital Adequacy Ratio (CAR) (X3) on murabahah financing (Y) in Islamic Commercial Banks for the period 2015-2019. The population in this study were all Sharia Commercial Banks recorded in the Financial Services Authority (OJK) for the 2015 2019 period. The sample of this study was 11 Islamic Commercial Banks from 14 total populations using quantitative methods with purposive sampling method. The analysis technique used in this research is descriptive statistical analysis, classic assumption test which includes normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Meanwhile, the data analysis used Multiple Regression, Determination Coefficient Test, Partial T Test, and Simultaneous F Test. The results of the T test showed that FDR and CAR partially had an effect on Murabahah Financing as long as the NPF variable had no significant effect on Murabahah Financing. Meanwhile, simultaneously there is a relationship between the variables FDR, NPF and CAR on Murabahah Financing together, these three variables have a significant effect on the variable murabahah financing.